Let the Game Begin: Ergodic as an Approach for Video Game Translation - SF. Lukfianka Sanjaya Purnama; SF. Luthfie Arguby Purnomo; Dyah Nugrahani (Register Journal, 2016)
This paper attempts to propose ergodic as an approach for video game translation. The word approach here refers to an approach for translation products and to an approach for the translation process. The steps to formulate ergodic as an approach are first, Aarseth’sergodic literature is reviewed to elicit a basis for comprehension toward its relationship with video games and video game translation Secondly, taking the translation of Electronic Arts’Need for Speed: Own the City, Midway’s Mortal Kombat: Unchained, and Konami’s Metal Gear Solid, ergodic based approach for video game translation is formulated. The formulation signifies that ergodic, as an approach for video game translation, revolves around the treatment of video games as a cybertext from which scriptons, textons, and traversal functions as the configurative mechanism influence the selection of translation strategies and the transferability of variables and traversal function, game aesthetics, and ludus and narrative of the games. The challenges countered when treating video games as a cybertext are the necessities for the translators to convey anamorphosis, mechanical and narrative hidden meaning of the analyzed frame, to consider the textonomy of the games, and at the same time to concern on GILT (Globalization, Internationalization, Localization, and Translation).KeywordsErgodic ; Translation Approach; Video Game Translation ; Textonomy; Anamorphosis